Answer:
31/3 ×51/4
527/4
Step-by-step explanation:
Hi i wanted to help you but i hate math do i am soooooooo sorry
V=x³-7x+6, V=(x-2)(x+3)*h
(x-2)(x+3)*h=x³-7x+6
h{x²+x-6}=x³-7x+6
h=(x³-7x+6)/(x²+x-6)
Therefore h=x-1
-----------------------------
Check answer:
V=(x-2)(x+3)(x-1)
=(x-1)(x²+x-6)
=x(x²+x-6)-1(x²+x-6)
=x³+x²-6x-x²-x+6
=x³-6x-x+6
=x³-7x+6
f(x) + g(x) =
4x + 3
3x^2 + 2x - 4
----------------------------------
3x^ +6x -1
Answer: 3x^ +6x -1
Either you typed something wrong in the problem or the answer
Answer:
First Question = 16 Second Question = 8
Step-by-step explanation:
First one
32+48=x(2+3)
80=5x
Divide each sides with 5 and you have x=16
Second one
32+48=4(x+12)
80=4x+48
subtract 48 from 48 and 80 and you have 32=4x.
Divide it with 4 both side and you have x=8